2020
DOI: 10.3389/fphy.2020.00300
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Quantum Field Theory: The Onset of Particle Motion and the Form of the Pilot Wave

Abstract: We consider the hydrodynamic quantum field theory proposed by Dagan and Bush, a model of quantum dynamics inspired by Louis de Broglie and informed by the hydrodynamic pilot-wave system discovered by Couder and Fort. According to this theory, a quantum particle has an internal vibration at twice the Compton frequency that generates disturbances in an ambient scalar field, the result being self-propulsion of the particle through a resonant interaction with its pilot-wave field. Particular attention is given her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…Prior work [21,22] has shown that the walking-droplet system is closer in form to de Broglie's original doublesolution pilot-wave theory [38], according to which a quantum particle has an internal vibration at the Compton frequency that generates its own guiding wave, and the resulting pilotwave dynamics gives rise to emergent statistics described by the standard quantum theory. Our study provides further motivation for the revisitation and extension of de Broglie's double-solution program, informed by the walking-droplet system [39][40][41][42].…”
mentioning
confidence: 87%
“…Prior work [21,22] has shown that the walking-droplet system is closer in form to de Broglie's original doublesolution pilot-wave theory [38], according to which a quantum particle has an internal vibration at the Compton frequency that generates its own guiding wave, and the resulting pilotwave dynamics gives rise to emergent statistics described by the standard quantum theory. Our study provides further motivation for the revisitation and extension of de Broglie's double-solution program, informed by the walking-droplet system [39][40][41][42].…”
mentioning
confidence: 87%
“…Prior work [21,22] has shown that the walking droplet system is closer in form to de Broglie's original doublesolution pilot-wave theory [37], according to which a quantum particle has an internal vibration at the Compton frequency that generates its own guiding wave, and the resulting pilot-wave dynamics gives rise to emergent statistics described by the standard quantum theory. Our study provides further motivation for the revisitation and extension of de Broglie's double-solution program, informed by the walking-droplet system [38][39][40][41].…”
Section: Introductionmentioning
confidence: 87%
“…De qualquer maneira "destacamos que nossos resultados não fecham a porta para a busca de difração e interferência das [gotas] errantes, apenas para as condições de contorno consideradas aqui, para o qual o comportamento do sistema é dominado pelas interações gota errante-anteparo" [37, p. 1152]. Além desse último artigo, vale a pena destacar outros trabalhos também de John W. M. Bush e colaboradores que têm se debruçado sobre essa analogia de maneira meticulosa, tal como o Hydrodynamic quantum field theory: the free particle e o Hydrodynamic quantum field theory: The onset of particle motion and the form of the pilot wave [38,39], a ponto de estabelecerem um modelo hidrodinâmico para a spintrônica em Emergent order in hydrodynamic spin lattices, observando uma histerese na transição de antiferromagnético para ferromagnético [40].…”
Section: Novo Interesse: As Gotas Errantesunclassified